Pemberdayaan TEFA Inovasi Kesehatan (V-Kes) melalui Pelatihan Rekam Medis Elektronik bagi Tenaga Kesehatan di Kabupaten Jember - Dony Setiawan Hendyca Putra; Mochammad Choirur Roziqin; Sabran; Tegar Wahyu Yudha Pratama; Ihwan Huda Al Mujib; Assyifa Itsnainia Mustika; Muhammad Ifantara Putra; Anggi Maulidya; Moh Lutfi Rizalul Hakim (SEJAGAT : Jurnal Pengabdian Masyarakat, 2025)
The uneven understanding and skills of health workers in the use of Electronic Medical Records (EMR) at the primary care level, especially in the Jember Regency, is a fundamental problem that hinders the acceleration of digital transformation in the health sector. This condition is further complicated by the mandatory implementation of EMR in accordance with Ministry of Health regulations, which also covers independent health worker practices, which are not yet fully understood and optimally responded to in the field. Additionally, access to practical and applicable EMR training remains limited, while the role of the Teaching Factory for Health Innovation (V-KES) as a digital health training center has not been fully utilized. The lack of post-training assistance has contributed to difficulties in implementing RME in daily practice, compounded by a low level of understanding of the urgency of transitioning from manual to digital systems, which affects the mental and technical readiness of health workers. Therefore, the solutions offered include 1) Conducting RME training based on hands-on practice, 2) Provision of modules or pocket books, dissemination of regulations in infographic or short video formats, 3) Utilization of the V-KES Teaching Factory as a simulation training center with Ministry of Health standard software, involvement of academic facilitators and health IT practitioners, as well as continuous online and offline assistance. This program will also be accompanied by strengthening the V-KES curriculum and promoting a digital mindset shift to support the full readiness of independent healthcare practitioners in implementing a nationally integrated RME system.